Phylogenetic relationships and larval morphology of the recently described diving beetle genus Laccomimus (Coleoptera: Dytiscidae: Laccophilinae) - Michat, Mariano Cruz (2015)
The larvae of the diving beetle genus Laccomimus Toledo & Michat, 2015 (Laccophilinae) are studied for the first time, based on detailed descriptions and illustrations of all instars of L. distinctus Toledo & Michat, 2015, with particular emphasis on morphometry and chaetotaxy. The phylogenetic relationships of this genus within the tribe Laccophilini are analyzed cladistically. Laccomimus is recovered as part of a clade that includes the genera Australphilus Watts, 1978, Neptosternus Sharp, 1882 and Laccophilus Leach, 1815 and is characterized by the presence of natatory setae on the tibia and tarsus, and within this clade it is a sister to the other genera. Third-instar larvae of Laccomimus and Africophilus Guignot, 1948 share the mediodistal insertion of the seta CO7 on the meso- and metacoxa, a short and spine-like seta TI6 on the metatibia, a ventrally sclerotized abdominal segment V and a short urogomphus. These characters are considered plesiomorphic and indicate a basal position of both genera within the Laccophilini. All instars of Laccomimus are characterized by the anterolateral lobes of the frontoclypeus clearly projecting beyond the anterior margin and the last abdominal segment strongly elongated. Diagnostic features of the first instar are: frontoclypeus unmodified posteriorly, lamellae clypeales thin and hair-like, pores ANe, MXb–d–f–i, LAb–c and seta TR3 absent, seta LA3 and an additional dorsal pore present on the prementum, abdominal tergites I–VII with anterior transverse carina, and ventral surface of the abdominal segment VI sclerotized.